2019
DOI: 10.1186/s12916-019-1399-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends of blood pressure and heart rate in normal pregnancies: a systematic review and meta-analysis

Abstract: Background Current reference ranges for blood pressure and heart rate throughout pregnancy have a poor evidence base. Methods This is a systematic review and meta-analysis. We included studies measuring blood pressure or heart rate from healthy pregnant women within defined gestational periods of 16 weeks or less. We analysed systolic blood pressure, diastolic blood pressure and heart rate by gestational age. We assessed effects of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 69 publications
7
62
0
5
Order By: Relevance
“…However, epidemiologic data are limited in the absence of defined diagnostic criteria for women with prepregnancy hypertension and/or proteinuria. Physiologic adaptations of pregnancy include a fall in BP, with a nadir in the second trimester, before rising again toward term (6). There is also gestational increase in proteinuria because of physiologic hyperfiltration and change in glomerular pore size (7,8).…”
Section: Definitions Of Preeclampsiamentioning
confidence: 99%
“…However, epidemiologic data are limited in the absence of defined diagnostic criteria for women with prepregnancy hypertension and/or proteinuria. Physiologic adaptations of pregnancy include a fall in BP, with a nadir in the second trimester, before rising again toward term (6). There is also gestational increase in proteinuria because of physiologic hyperfiltration and change in glomerular pore size (7,8).…”
Section: Definitions Of Preeclampsiamentioning
confidence: 99%
“…A systematic review published in 2019 also reported that DBP was lowest at 21 weeks in women with normal pregnancies, but the lowest SBP was found at 10 weeks. The findings of this systematic review, however, were inconclusive because of substantial heterogeneity in the racial and social characteristics of the pregnant women in the study, study design, and time and method of BP measurements 20 …”
Section: Discussionmentioning
confidence: 83%
“…In our previous systematic review, we could not find reliable estimations of the outer centiles of heart rate postpartum. 6 In our previous work with the 4P cohort, heart rates higher than 100 bpm occurred in more than 10% of women at 40 weeks of gestation. 25 Postpartum heart rates of greater than 100 bpm were much less common, with the 90th centile for heart rate 100 bpm or less from day 1 postpartum.…”
Section: Discussionmentioning
confidence: 86%
“… 5 Identification of physiologic deterioration postpartum needs improvement, 4 but normal vital sign ranges are poorly defined. 6 Previous studies usually report values on one or two occasions often several weeks postpartum. 7 14 Daily data are rare, often small-scale, and outdated (Walters BNJ, Walters T. Hypertension in the puerperium [letter].…”
mentioning
confidence: 99%
See 1 more Smart Citation